Application of cluster-associative model for calculation of kinematic viscosity of metal melts - Kazhikenova, A.Sh.; Alibiyev, D.B.; Seitimbetova, A.B.; Smailova, A.S. (KSU Publ., 2020)
Metal melts are often used in the national economy and industry. Therefore the study of the physicochemical properties of metals is given great attention. Especially researchers pay great attention to the study of viscosity, since viscosity is of great practical importance in metallurgy. Studying the viscosity of molten metal, at the same time, is essential scientific interest, since viscosity is the most structurally sensitive characteristic of the melt. The study of viscosity through experiment is somewhat difficult because many metals melt at very high temperatures. It is difficult to create such conditions without special equipment. Therefore many researchers are looking for additional development based on alternative approaches to understanding viscosity. The authors in their article consider a new concept of randomized particles and on this basis propose a cluster-associate model for calculating viscosity without conducting an experiment. The authors give examples of calculating the kinematic viscosity of some metals according to the model proposed in this paper. The results we received show that the proposed model allows us to calculate the viscosity even at very high temperatures. A comparison of the obtained results with experimental data shows the functionality of the proposed model. The proposed model can be used to calculate the viscosity of liquid metals in a wide temperature range. The article also shows the possibility of using this model for calculating the activation energy of a viscous melt flow.
Кинематикалық тұтқыр сұйық металға кластерлі-ассоциативті модельді қолданудың тиімділігі
Кинематикалық тұтқыр сұйық металға кластерлі-ассоциативті модельді қолданудың тиімділігі
Keywords: viscosity; chaotized particles; the degree of clusters association; cluster-associated model; liquid metals; reference point; crystal-moving particles; the temperature dependences of the viscosity